Manajemen Strategi Peningkatan Mutu Layanan Di Kantor Urusan Agama Kecamatan Ambal Kabupaten Kebumen - Akh. Kheroni (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2023)
Strategic Management in improving the quality of service at the Office of Religious Affairs in Ambal District, Kebumen Regency. The purpose of this study was to find out the strategic management carried out by the Office of Religious Affairs in Ambal District, Kebumen Regency, especially marriage services and the quality of premarital guidance services from the implementation of this management strategy in the Office of Religious Affairs in Ambal District, Kebumen Regency. This study uses a qualitative research method with a case study research type. The data analysis used is the Miles and Huberman Interactive analysis model. The results showed that strategic management carried out by the Office of Religious Affairs in Ambal District, Kebumen Regency was also applied to personnel services based on the Provincial RPJP and RPJMD of the Ministry of Religion, Kebumen Regency, through the process of strategic planning stages, strategy implementation and strategy evaluation. And the service quality of the Office of Religious Affairs in Ambal District, Kebumen Regency, after strategic management has been carried out, is quite good, which is proven by referring to the fulfillment of the five main dimensions of service quality.